Ocimum basilicum L. associated bacteria with antifungal activity - Arce-Amezquita, Pablo Misael; Romero-Bastidas, Mirella; Rojas-Contreras, Maurilia (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The presence of pathogens, like fungi, is one of the most important causes of basil crop loss around the world; however, many microorganisms have a crucial role on plant development including protection against pathogenic ones. In the present study, basil associated bacteria were isolated, quantified and preserved. Characterization of isolated bacteria showed 165 Gram positive strains, 152 with bacillary and 13 with coccoid morphology. Later, in vitro antagonism assays were performed, first against Aspergillus spp. and then against Neoscytalidium dimidiatum, Alternaria spp. and Aspergillus spp. Finally, the effect of the isolated bacteria on basil seed germination and first stages of development were carried out. Sampled basil plants, produced around La Paz, Baja California Sur, Mexico, were colonized by known antagonistic bacteria of the Bacillus genus. Bacillus amyloliquefaciens strains were the prevailing species with antifungal activity. Moreover, strains ALMH42, ALMR73 and ALAH91 did not show any deleterious effect on basil seedling development. Biotechnological potential exploration of these isolated strains from healthy basil plants is of great interest for future applications on this and other crops.